Reconstructing orbits of galaxies in extreme regions (ROGER) - II: Reliability of projected phase-space in our understanding of galaxy populations - Coenda, Valeria; Rios, Martín De Los [UNESP]; Muriel, Hernán; Cora, Sofiá A; Martínez, Hcrossed D Sign©ctor J; Ruiz, Andrcrossed D Sign©s N; Vega-Martínez, Cristian A (Oxford University Press (OUP), 2022)
We connect galaxy properties with their orbital classification by analysing a sample of galaxies with stellar mass M⋆ ≥ 108.5h-1M⊙ residing in and around massive and isolated galaxy clusters with mass M200 > 1015h-1M⊙ at redshift z = 0. The galaxy population is generated by applying the semi-analytic model of galaxy formation sag on the cosmological simulation MultiDark Planck 2. We classify galaxies considering their real orbits (3D) and their projected phase-space position using the roger code (2D). We define five categories: cluster galaxies, galaxies that have recently fallen into a cluster, backsplash galaxies, infalling galaxies, and interloper galaxies. For each class, we analyse the 0.1(g - r) colour, the specific star formation rate (sSFR), and the stellar age, as a function of the stellar mass. For the 3D classes, we find that cluster galaxies have the lowest sSFR, and are the reddest and the oldest, as expected from environmental effects. Backsplash galaxies have properties intermediate between the cluster and recent infaller galaxies. For each 2D class, we find an important contamination by other classes. We find it necessary to separate the galaxy populations in red and blue to perform a more realistic analysis of the 2D data. For the red population, the 2D results are in good agreement with the 3D predictions. Nevertheless, when the blue population is considered, the 2D analysis only provides reliable results for recent infallers, infalling galaxies and interloper galaxies.
Keywords: galaxies: clusters: general; galaxies: haloes; galaxies: kinematics and dynamics; methods: analytical; methods: numerical